FISHERY AND BIOLOGY OF THE OIL SARDINE AT KARWAR - Annigeri, G G (Indian Journal of Fisheries, 2011)
The oil sardine fishery at Karwar showed erratic fluctuations during the years of study,from an annual landing figure of 4.41 tonnes in 1964-65 to 250.06 tonnes in 1967-68.The average, based on the earlier 14 years' catch worked out to 91.21 tonnes. The threelength frequency modes at 135-140, 160-165 and 185-190 mm have been interpreted tocorrespond to I, II and III age groups. The fish attains maturity at about 140 mmand the spawning season lasts from July-August to November-December. This is alsosupported by the trend of change in 'K' values. A good fishery season seems relatedto the temperature range of 27-29.5Â°C, lower salinity and a low phosphate content inthe water